Communication between primary and secondary care: deficits and danger. (2nd August 2019) - Dinsdale, Elsa; Hannigan, Ailish; O'Connor, Ray; O'Doherty, Jane; Glynn, Liam; Casey, Monica; Hayes, Peter; Kelly, Dervla; Cullen, Walter; O'Regan, Andrew
Abstract: Background: Timely and accurate communication between primary and secondary care is essential for delivering high-quality patient care. Objective: The aim of this study is to evaluate the content contained in both referral and response letters between primary and secondary care and measure this against the recommended national guidelines. Methods: Using an observational design, senior medical students and their general practice supervisors applied practice management software to identify 100 randomly selected adults, aged greater than 50 years, from a generated list of consults over a 2-year period (2013–2015). All data included in referral and response letters for these adults were examined and compared with the gold standard templates that were informed by international guidelines. Results: Data from 3293 referral letters and 2468 response letters from 68 general practices and 17 hospitals were analysed. The median time that had elapsed between a patient being referred and receiving a response letter was 4 weeks, ranging from 1 week for Emergency Department referral letters to 7 weeks for orthopaedic surgery referral letters. Referral letters included the reason for referral (98%), history of complaint (90%) and current medications (82%). Less commonly included were management prior to referral (65%) and medication allergies (57%). The majority of response letters included information on investigations (73%), results (70%) and follow-up plan (85%). Less commonly, response letters included medication changes (30%), medication lists (33%) and secondary diagnoses (13%). Conclusions: Future research should be aimed at developing robust strategies to addressing communication gaps reported in this study.